Extracting damping information from resilient modulus tests - Pereira, Claudio (2017)
In addition to the dynamic moduli, the damping properties of the different pavement layers are required by most algorithms used for modeling the dynamic responses of pavement caused by moving or impact loads. The importance of the damping properties in estimating the proper responses is well documented in the geotechnical engineering community. The dynamic moduli are typically estimated in the laboratory using the cyclic triaxial (resilient modulus) tests. The feasibility of estimating the damping properties with resilient modulus tests is explored in this paper. The most promising algorithm among the alternatives studied was preliminarily established from the resilient modulus tests carried out on 17 gravel bases, sandy subgrades, and clayey subgrades. The selected method was used to develop a database for further evaluation. The damping coefficient was correlated to the applied stresses, the measured strains, and the nonlinear stiffness parameters (k(1)-k(3)) obtained from a nonlinear constitutive model commonly used in mechanistic-empirical pavement analysis methodology.